Hungarian – Italian bilingual education in the light of public education policy - Papp Beáta (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. Four sectors of the education system are distinguished: public education, vocational training, higher education and adult education. In my dissertation, I intend to focus only on public education. Hungarian-Italian relations date back a long time. In my study, through the magnifying glass of education policy, I present the situation of the Italian language in the language policy between the 18th and 20th centuries in a language policy approach. Next, through the lens of language policy, I will describe the new type of school that emerged in the years around the change of regime, the bilingual school, and the circumstances of its establishment. Finally, I touch on the status of the Italian language in the 20th century, with an emphasis on secondary education.
Magyar – olasz két tannyelvű oktatás a közoktatáspolitika tükrében
Keywords: language policy; bilingual education; Italian language